Lay activism and the high church movement of the late eighteenth century : the life and thought of William Stevens, 1732-1807 - Andrews, Robert M. (Honorary Research Associate) (Brill's series in church history, 2015)
In Lay Activism and the High Church Movement of the Late Eighteenth Century, Robert M. Andrews presents a biography of the late eighteenth-century High Church layman, William Stevens (1732-1807), elucidating his influence within the High Church movement of his day.